Developments in EDM process variables - Khan, Ahsan Ali; Mohammed, Baba Ndaliman; Mohammad , Yeakub Ali (International Islamic University Malaysia, 2011)
Abstract. The electrical discharge machining (EDM) process parameters (both the input and output) are presented. The input variable of EDM presented here are electrical and non-electrical ones. These are peak current, discharge voltage, pulse cycles (duration and interval), electrode‘s polarity and gap. The recent advances in areas of both the input and output variables are also presented. The use of powder metallurgy (PM) electrodes and the effects of mixing conductive powders in dielectrics are among the advancements in EDM process.